1977
DOI: 10.1164/arrd.1977.116.4.695
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Secretion by Tracheal Explants Cultured from Rats Exposed to Ozone1–2

Abstract: Tracheal explants from rats exposed to 0.8 ppm (1.9 mg per m3) of ozone 8 hours per day for 1 to 90 days were incubated in culture with glucosamine labeled with carbon-14 or hydrogen-3. Compared with tracheas from control rats exposed to filtered air, the explants demonstrated a decreased rate of glycoprotein secretion for exposure intervals of as long as one week, followed by a rebound to an increased rate of glycoprotein secretion for at least 12 weeks of continued exposure to ozone. Detailed study of the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The response in the rat is most likely due to an increase in secretion, but could be totally or partially due to a decrease in production. Exposures of tracheal explants to various concentrations of ozone have demonstrated that this irritant is an in vitro secretogogue for intraepithelial mucus (10). It has also been reported that tracheal secretory cells from monkeys exposed to 0.64 ppm ozone for 3 or 7 days were much smaller than those in air controls, due to a decrease in cytoplasmic secretory granules (16).…”
Section: Discussionmentioning
confidence: 98%
“…The response in the rat is most likely due to an increase in secretion, but could be totally or partially due to a decrease in production. Exposures of tracheal explants to various concentrations of ozone have demonstrated that this irritant is an in vitro secretogogue for intraepithelial mucus (10). It has also been reported that tracheal secretory cells from monkeys exposed to 0.64 ppm ozone for 3 or 7 days were much smaller than those in air controls, due to a decrease in cytoplasmic secretory granules (16).…”
Section: Discussionmentioning
confidence: 98%
“…We have focused our attention on short-term (22 h) incubation of tissue as opposed to the 7-10 days, which is customarily used by others. Our rationale for this was that Boat et al have shown a decrease in the rate of secretion of glycoproteins after one day in culture for nasal polyps (2) and for tracheal tissue (5), which we wanted to avoid so as to enable rates of secretion to be directly compared between experiments, although we should point out that the time course of glycoprotein secretion apparently remains linear for at least 72-96 h in our system thus allowing rates to be determined as the slope of such lines over this entire interval (10,15). In addition, shortterm incubations in culture seem more likely to accurately mirror the metabolic capacities of the tissue in vivo.…”
Section: Methodsmentioning
confidence: 99%
“…We have published (15) evidence that chronic exposure of rats to ozone causes changes in the ratio of the two peaks from a BioGel AlSOm column, such that the lower molecular weight included peak is augmented at the expense of the first peak, as shown in Figure 7. In simpler terms, there was a shift in the relative number ofcounts from peak I to peak II upon exposure of the rats to ozone in those experiments.…”
Section: Incubated Tissuementioning
confidence: 99%
“…The ratio of glycoproteins in the two peaks has been used by others (4), as well as by ourselves (15), as a probe for observing changes in the structure of glycoproteins being secreted by tracheal explants. We have published (15) evidence that chronic exposure of rats to ozone causes changes in the ratio of the two peaks from a BioGel AlSOm column, such that the lower molecular weight included peak is augmented at the expense of the first peak, as shown in Figure 7.…”
Section: Incubated Tissuementioning
confidence: 99%